Correlation of Anxiety Level, Concentration, and Kinesthetic Perception with Accuracy of Volleyball Jump Serve - Purwo Abdullah Nur Gofur; Amrulloh, Aziz (Universitas PGRI Palembang, 2025)
With the accuracy of jump serves among male volleyball players of the SBV Popsi Sragen Club. Technical execution in volleyball, particularly the jump serve, requires not only physical skill but also psychological readiness and sensory-motor awareness. Anxiety may interfere with motor coordination and focus, while concentration and kinesthetic perception play key roles in movement control and targeting accuracy. This research employed a quantitative correlational method, involving 20 male players selected through a total sampling approach. Instruments included the Sport Competition Anxiety Test (SCAT) for measuring anxiety, a grid concentration test to assess attention focus, and a kinesthetic perception test based on position-matching tasks. Jump serve accuracy was evaluated through practical testing using a scoring system targeting specific court zones. Data analysis using Pearson Product-Moment correlation revealed significant relationships between anxiety, concentration, and kinesthetic perception with jump serve accuracy (p < 0.05). These findings emphasize the importance of integrating psychological and perceptual training into volleyball coaching programs to improve service performance.